Dysglycemia associated with quinolones. Issue 3 (June 2015) - El Ghandour, Sarah; Azar, Sami T.
Highlights: Hyperglycemia and hypoglycemia are associated with antimicrobials use. Fluoroquinolones is the most reported to cause dysglycemia. Mechanisms explaining dysglycemia are discussed. Abstract: Antimicrobial therapy is well known to be associated with fluctuations of blood glucose levels. This review aims at exploring the association between glycemic fluctuations and antibiotics mainly focusing on quinolones. Quinolones are associated with hypoglycemia and hyperglycemia. Several mechanism are proposed to explain this causality.